Mati Klarwein : Improved Paintings 1979-2000 - Bramly, Serge (Palma de Mallorca : Max Publishing, 2000)
The paintings in this book have been purchased by Mati Klarwein at the flea markets and thrift stores of Los Angeles, Manhattan, Paris, Palma de Mallorca and Barcelona for prices not exceeding those of a virgin canvas of equal size from any art material store. Because a painting is always and never finished, Klarwein continues to paint into them by stepping out of his own mind and simulating the style of the original artist as best he can, thus displacing them from their role as a purely visual product to put them at The service of the mind so to speak. Saving them from oblivion he reintegrates them into our ongoing art dialogue. This book is highly subversive and is not recommended for zombies over 13 years old.
improved paintings exhibitions, bibliog. Mati Klarwein, libros publicados Felipe Hernández, biog. Serge Bramly p. 98
Engels
Spaans
boek
Keywords: Klarwein, Mati